THE ROLE OF ENVIRONMENTAL ACCOUNTING IN IMPROVING ENVIRONMENTAL PERFORMANCE THROUGH CSR DISCLOSURE - Nicholas Renaldo; Fadrul Fadrul; Suhardjo Suhardjo; Andi Andi; Tandy Sevendy; Hinsatopa Simatupang (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The purpose of this study, namely, to determine the effect of environmental accounting on environmental performance with Corporate Social Responsibility as an intervening variable in plantation companies listed on the Indonesian Stock Exchange, which is expected to provide insights to the plantation industry to formulate adequate environmental disclosure. This study uses secondary data in the form of annual reports and PROPER assessment results issued by the Ministry of Environment and Forestry on plantation companies listed on the Indonesian Stock Exchange. The sampling technique used in this study was purposive sampling with the analytical method in this study through path analysis and to determine the effect of the variables involved in the study, the Sobel test was used. The results show that environmental accounting has a positive effect on environmental performance, the better the application of environmental accounting, the more environmental performance will increase, then corporate social responsibility has a positive effect on environmental performance, the higher the value From the disclosure of corporate social responsibility, the value of environmental performance will also increase, and corporate social responsibility as an intervening variable may mediate the relationship between environmental accounting and environmental performance.